2023
DOI: 10.3389/fcvm.2023.1105342
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative non-high-density lipoprotein cholesterol burden and risk of atherosclerotic cardiovascular disease: a prospective community-based study

Abstract: BackgroundThe relationship between cumulative non-high-density lipoprotein cholesterol (non-HDL-C) burden and atherosclerotic cardiovascular disease (ASCVD) remains unclearObjectiveTo prospectively examine the association between cumulative non-HDL-C burden and ASCVD risk in the Kailuan cohort of China.MethodsA total of 49,679 subjects who were free of ASCVD participated in three consecutive examinations in 2006, 2008 and 2010 were enrolled. Duration and concentration of cumulative exposure to non-HDL-C (cumNo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Non‐HDL‐C has also been recommended by American College of Cardiology/American Heart Association 6 and European Society of Cardiology/European Atherosclerosis Society guidelines 2 for CVD risk assessment, given its association with incident CVD in different populations, including those from Europe, Australia, North America, 58 and China. 59 , 60 Finally, 3 lipid components within IDL, IDL‐C, IDL‐FC, and IDL‐phospholipids, showed positive associations with incident CHD in this study and MESA, 25 whereas UK Biobank reported inverse associations for IDL‐FC and IDL‐phospholipids. 24 Therefore, more studies are needed to clarify the role of IDL lipid components in predicting CHD risk.…”
Section: Discussionmentioning
confidence: 46%
“…Non‐HDL‐C has also been recommended by American College of Cardiology/American Heart Association 6 and European Society of Cardiology/European Atherosclerosis Society guidelines 2 for CVD risk assessment, given its association with incident CVD in different populations, including those from Europe, Australia, North America, 58 and China. 59 , 60 Finally, 3 lipid components within IDL, IDL‐C, IDL‐FC, and IDL‐phospholipids, showed positive associations with incident CHD in this study and MESA, 25 whereas UK Biobank reported inverse associations for IDL‐FC and IDL‐phospholipids. 24 Therefore, more studies are needed to clarify the role of IDL lipid components in predicting CHD risk.…”
Section: Discussionmentioning
confidence: 46%
“…Non-HDL-C is an estimate of the total amount of pro-atherogenic apolipoprotein B (ApoB)–containing lipoproteins, including very low– and low-density lipoproteins (LDL) [ 26 ]. Numerous studies have shown that non-HDL-C is significantly associated with an elevated risk of atherosclerotic cardiovascular disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%